Enhancing Thermal Comfort Through Hand Warmer Application in Patients Undergoing Regional Anesthesia: A Pre-Experimental Study - Muhammad Hirzi Syafiqri; Aisyah Nur Azizah; Triyas Singgih Pambudi (Fakultas Kesehatan, Universitas Nurul Jadid, 2026)
Background: Patients undergoing regional anesthesia are frequently exposed to low perioperative ambient temperatures before surgery, increasing the risk of thermal discomfort even in the absence of overt hypothermia. Although perioperative warming strategies have been widely discussed, evidence regarding simple localized warming interventions during the pre-anesthetic phase remains limited, particularly in relation to subjective thermal comfort. Objective: To examine the effect of hand warmer application on thermal comfort among patients undergoing regional anesthesia during the pre-anesthetic phase. Methods: A pre-experimental study with a one-group pretest–posttest design was conducted at PKU Muhammadiyah Bantul Hospital, Indonesia. Thirty patients scheduled for regional anesthesia were recruited using purposive sampling. Thermal comfort was assessed before and after intervention using the Thermal Comfort Scale (TCS). Participants received localized warming through hand warmer application on the palmar area for 10 minutes during the pre-anesthetic waiting period. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05.Results: Prior to the intervention, most participants reported neutral (43.3%) or uncomfortable (40.0%) thermal sensations. Following hand warmer application, thermal comfort shifted entirely toward comfortable (73.3%) and very comfortable (26.7%) categories. Wilcoxon signed-rank analysis demonstrated a statistically significant improvement in thermal comfort scores after the intervention (Z = −4.861, p < 0.001). No participants reported worsening thermal comfort following localized warming.Conclusion: Hand warmer application improved subjective thermal comfort among patients undergoing regional anesthesia during the pre-anesthetic phase. As a simple, low-cost, and non-invasive intervention, localized peripheral warming may support more patient-centered perioperative nursing care and enhance pre-anesthetic comfort management.